Endocrine Manifestations in Children and Adolescents with Thalassemia Major - A Prospective Cohort Study - Salunkhe, Manasi; Sajjan, Shruti; Sajjan, Anilkumar; Patil, M.M. (International Journal of Child Health and Nutrition, 2025)
Background: Thalassemia major is a widely prevalent genetic hemoglobinopathy marked by inadequate erythropoiesis and persistent hemolytic anemia. Although frequent blood transfusions are life-saving, such therapy leads to accumulated iron excess, which impacts multiple organs, including the endocrine glands. Despite progress in iron chelation therapy, endocrinopathies continue to be a considerable source of morbidity in individuals with thalassemia major. Objective: This article explores the endocrine manifestations in children and adolescents with thalassemia major and identifies associated risk factors. Methods: This study included 51 children and adolescents with a thalassemia major attending the clinic. The researchers recorded a detailed history of each participant, made an anthropometric assessment, and conducted a clinical examination. Furthermore, laboratory investigations were performed to measure each participant’s complete blood count, serum ferritin, glucose parameters (FBS, PPBS, HbA1c), thyroid function (T3, T4, TSH), serum calcium, and gonadotropin levels (LH, FSH) in children >13 years of age. Results: Within the study population, 74.5% had initiated transfusions before one year of age, and 88.2% received monthly transfusions. Growth retardation was evident, with 23.5% and 29.4% having weight and height, respectively, below the third centile. Endocrine abnormalities included diabetes (25.5%), hypothyroidism (9.8%), hypogonadotropic hypogonadism (25% with low LH and 12.5% with low FSH) in children >13 years of age (n=8), and hypocalcemia (21.6%). Serum ferritin was elevated (> 1500 ng/mL) in 90.2% of patients. Significant associations were observed between HbA1c levels and chelation therapy (p < 0.001), as well as hypogonadism and chelation therapy (p = 0.005). Multiple endocrinopathies (> 2) were observed in 11.7% of patients. Conclusion: Endocrine complications are common in pediatric thalassemia major patients, and glucose metabolism abnormalities are the most prevalent. Age, transfusion burden, and chelation therapy significantly influence the risk of endocrinopathies. Regular monitoring of endocrine function and appropriate interventions are essential for improving the quality of life and reducing morbidity in these patients.